The Psychological Effects of the COVID-19 on Students Who Choose the Medical Profession With Different Motivational Factors: A Cross-Sectional Study - Ozlem Terzi MD; Hatice Nilden Arslan MD, Assoc Prof; Ozlem Midik MD, Assoc Prof; Cihad Dundar MD, Prof (SAGE Publishing, 2022)
The COVID-19 pandemic has generated mental and psychological health problems worldwide. The aim of this study was to determine whether the psychological effects of COVID-19 were different in medical students who chose the medical profession with different motivational factors. In the study, there were 389 medical school students. The survey asks about sociodemographic features and the students' reasons for choosing the medical profession. The study also included a self-assessed Hospital Anxiety-Depression Scale and Beck Hopelessness Scale. While 41% of students chose the medical profession for economic reasons, the ratio of whom have an extrinsic and intrinsic source of motivation was 37% and 22%, respectively. It was found that there was a statistically significant difference in the distribution of motivational factors by gender. Almost 50% of males were affected by economic motivation factors. The difference in motivational factors between genders was found to be statistically significant. Anxiety in females, depression in students with low-income families, and hopelessness in students older than 22 years and interns were higher than in the others ( P  < .05). Median scores for anxiety, depression, and hopelessness were higher for students with extrinsic motivational sources. However, only the difference in scores of anxiety and hopelessness was found statistically significant ( P  < .05). We found that the psychological effects of the COVID-19 pandemic varied according to both sociodemographic characteristics of the medical students and reasons for choosing medical profession. According to our results, the idealistic students interested in the medical profession, who want to support others and prioritize economic benefits, had fewer psychological issues than those who chose the medical profession due to family pressure or external factors.